Positron Emission Tomography-Computed Tomography Surveillance after (Chemo)Radiotherapy in Advanced Head and Neck Squamous Cell Cancer: Beyond the PET-NECK Protocol. Issue 10 (October 2020) - Zhou, S.; Rulach, R.; Hendry, F.; Stobo, D.; James, A.; Dempsey, M.-F.; Grose, D.; Lamb, C.; Schipani, S.; Rizwanullah, M.; Wilson, C.; Lau, Y.C.; et al.
Abstract: Aims: To evaluate the implementation of 18-fluorodeoxyglucose positron emission tomography-computed tomography (FDG PET-CT) surveillance after (chemo)radiotherapy, to compare outcomes for those who achieved a complete (CR), equivocal (EQR) and incomplete (ICR) nodal response on 12-week PET-CT according to their human papillomavirus (HPV) status, and to assess the safety of ongoing surveillance beyond 12 weeks in the HPV-positive EQR group. Materials and methods: All patients with node-positive head and neck squamous cell carcinoma (HNSCC) treated with (chemo)radiotherapy between January 2013 and September 2017 were identified. PET-CT responses were classified as CR, ICR or EQR. Patient outcomes were obtained from electronic records. Results: In total, 236 patients with a minimum of 2 years of follow-up were identified. The mean age was 59 years; 79.3% had N2 disease; 77.1% of patients had oropharyngeal cancer and 10.1% had squamous cell carcinoma of unknown primary, of whom 82.0% (169) were HPV positive; 78.0% received chemoradiotherapy. The median time from the end of radiotherapy to PET-CT was 91 days. Of the HPV-related HNSCC, 60.4% achieved CR, 29.0% EQR and 10.6% ICR. With a median follow-up of 41.7 months, there was no difference in survival between patients with HPV-related HNSCC achieving CR and EQR (median overall survival not reached for both, P  = 0.67) despite the omission of immediate neck dissection in 98.0% of the EQR group. Conclusion: Patients with HPV-positive HNSCC who have achieved EQR have comparable survival outcomes to those who achieved a CR despite the omission of immediate neck dissections; this shows the safety of ongoing surveillance beyond 12 weeks in this group of patients. Highlights: Two-year overall survival and locoregional control in our cohort was similar to the PET-NECK study. No immediate neck dissections were carried out in 98.0% of HPV-positive EQRs. No difference in survival was noted between HPV-positive CRs and EQRs. Thus extended surveillance without immediate neck dissection would be appropriate in this group.